FLESHY FUNGI OF NORTH-WESTERN HIMALAY AS-V* - T. N. LAKHANPAL, R. P BHATT AND (Indian Phytopathology, 2002)
Three species of Laclarius, namely, L. camphoratus, L. corrugis and L. piperatus are described and illustrated. All are new records for India